85.2k views
1 vote
PLEASE HELP ME!!!!!!!!!!!!!!!!

PLEASE HELP ME!!!!!!!!!!!!!!!!-example-1

2 Answers

1 vote

Answer:

A

Explanation:

Each term in the second factor is multiplied by each term in the first factor, that is

(2y - 3)(3y - 2)

= 2y(3y - 2) - 3(3y - 2) ← distribute both parenthesis

= 6y² - 4y - 9y + 6 ← collect like terms

= 6y² - 13y + 6 → A

User Igor Toporet
by
5.9k points
3 votes

A. 6y^2 - 13y + 6

Use the FOIL method of multiplying binomials.

First monomial in each binomial: 2y * 3y = 6y^2

Outside monomials: 2y * -2 = -4y

Inside monomials: -3 * 3y = -9y

Last monomial in each binomial: -3 * -2 = 6

Finally, add everything together. 6y^2 - 4y - 9y + 6

Simplify to 6y^2 - 13y + 6

User Jen Born
by
5.1k points